Ultraviolet B irradiation increases the expression of inflammatory cytokines in cultured sebocytes. Issue 12 (4th December 2013) - Lee, Weon Ju; Park, Kyung Hea; Sohn, Mi Yeung; Lee, Won Chae; Lee, Seok‐Jong; Kim, Do Won
Abstract Sebaceous gland hyperplasia and increased sebum secretion after irradiation of ultraviolet (UV)‐B has been widely accepted. This study was performed to clarify expression of inflammatory cytokines after irradiating UV‐B in cultured sebocytes. Reverse transcription polymerase chain reaction was performed to measure gene expression of inflammatory cytokines, including interleukin (IL)‐1β, IL‐6, IL‐8 and tumor necrosis factor‐α, in cultured sebocytes after exposure to 40 and 70 mJ/cm2 UV‐B. Protein expression of inflammatory cytokines and lipid production in cultured sebocytes after exposure to UV‐B were measured using enzyme‐linked immunoassay and lipid analysis kit. The expression of inflammatory cytokines, especially IL‐1β and IL‐8, was significantly increased in cultured sebocytes after treatment with UV‐B. Many more studies on the effect of UV‐B on sebaceous glands should be performed to reveal the pathogenic mechanism of acne.